Plant competition cues activate a singlet oxygen signaling pathway in Arabidopsis thaliana - Berardi, Nicole; Amirsadeghi, Sasan; Swanton, Clarence J. (Frontiers in Plant Science, 2024)
Oxidative stress responses of Arabidopsis to reflected low red to far-red signals (R:FR ≈ 0.3) generated by neighboring weeds or an artificial source of FR light were compared with a weed-free control (R:FR ≈1.6). In the low R:FR treatments, induction of the shade avoidance responses (SAR) coincided with increased leaf production of singlet oxygen (1O2). This 1O2 increase was not due to protochlorophyllide accumulation and did not cause cell death. Chemical treatments, however, with 5-aminolevulinic acid (the precursor of tetrapyrrole biosynthesis) and glutathione (a quinone A reductant) enhanced cell death and growth inhibition. RNA sequencing revealed that transcriptome responses to the reflected low R:FR light treatments minimally resembled previously known Arabidopsis1O2 generating systems that rapidly generate 1O2 following a dark to light transfer. The upregulation of only a few early 1O2 responsive genes (6 out of 1931) in the reflected low R:FR treatments suggested specificity of the 1O2 signaling. Moreover, increased expression of two enzyme genes, the SULFOTRANSFERASE ST2A (ST2a) and the early 1O2-responsive IAA-LEUCINE RESISTANCE (ILR)-LIKE6 (ILL6), which negatively regulate jasmonate level, suggested that repression of bioactive JAs may promote the shade avoidance (versus defense) and 1O2 acclimation (versus cell death) responses to neighboring weeds.